2015
DOI: 10.1101/gr.186882.114
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals pathogenic mutations in 91 strains of mice with Mendelian disorders

Abstract: Spontaneously arising mouse mutations have served as the foundation for understanding gene function for more than 100 years. We have used exome sequencing in an effort to identify the causative mutations for 172 distinct, spontaneously arising mouse models of Mendelian disorders, including a broad range of clinically relevant phenotypes. To analyze the resulting data, we developed an analytics pipeline that is optimized for mouse exome data and a variation database that allows for reproducible, user-defined da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 46 publications
1
62
0
1
Order By: Relevance
“…We used this approach to identify alleles of Alx4 ( lst-2J ) and Pfas ( Sofa-3J ), among others. A majority of our mutant lines enter a standardized HTS exome pipeline to identify putative causative mutations (Fairfield et al, 2011b; Fairfield et al, 2015). This has proven very successful, and more than half (18) of our 33 new mutant genes were identified using this approach (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used this approach to identify alleles of Alx4 ( lst-2J ) and Pfas ( Sofa-3J ), among others. A majority of our mutant lines enter a standardized HTS exome pipeline to identify putative causative mutations (Fairfield et al, 2011b; Fairfield et al, 2015). This has proven very successful, and more than half (18) of our 33 new mutant genes were identified using this approach (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…A mapping panel of 100 N:J substrain SNPs indicated a strong linkage to 11-114979024-S with an estimated LOD (score of 9.4308 (significance is LOD ≥ 3) and 37 of 38 animals were concordant with this marker. Whole exome sequencing (Fairfield et al, 2015) revealed a single mismatch allele of C to T on chromosome 11: 112,782,845 on (GRCm38/mm10). The SNV, located in exon one of SRY-box containing 9 ( Sox9 ), is predicted to result in the missense mutation T87M (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sakaguchi et al have described a mouse substrain showing spontaneously developed rheumatoid arthritis phenotype (SKG mice); subsequently SKG mice were shown to have a point mutation in ZAP-70 gene [15]. Additionally, recent exome sequencing revealed pathogenic mutations in 91 strains of mice with Mendelian disorders [16]. Similarly, 4T1-S line might have a substantial mutation which altered its immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, the neurologic phenotype and severe hearing loss are also observed in other Ap3d1 mutant strains that do not carry these additional mutations. 37 Third, we show that the identified mutation significantly reduces expression levels of the AP3d protein. Apparently this has severe consequences for the stability of the AP3 complex because the other subunits (AP3b3A, AP3s, and AP3m) were also decreased in protein expression.…”
Section: Discussionmentioning
confidence: 99%